2009
DOI: 10.1016/j.aquaculture.2009.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal anomalies in dusky grouper Epinephelus marginatus (Lowe 1834) juveniles reared with different methodologies and larval densities

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.A C C E P T E D M A N U S C R I P T Skeletal anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 24 publications
(21 reference statements)
2
57
0
3
Order By: Relevance
“…It may be for the reason that tiger puffer has more interspecific aggression than river puffer. Meanwhile, previous studies have reported that stocking density affected skeletal anomalies (Boglione et al 2009), metamorphosis (Hosfeld et al 2009), sex ratios (Saillant et al 2003), gonad development Claudia et al 2004, egg production (Peck andHolste 2006), skin pigmentation (Doolan et al 2008), and survival (Tagawa et al 2004) on various fishes.…”
Section: Discussionmentioning
confidence: 99%
“…It may be for the reason that tiger puffer has more interspecific aggression than river puffer. Meanwhile, previous studies have reported that stocking density affected skeletal anomalies (Boglione et al 2009), metamorphosis (Hosfeld et al 2009), sex ratios (Saillant et al 2003), gonad development Claudia et al 2004, egg production (Peck andHolste 2006), skin pigmentation (Doolan et al 2008), and survival (Tagawa et al 2004) on various fishes.…”
Section: Discussionmentioning
confidence: 99%
“…De esta forma, modificando las condiciones de luz junto con el uso de la técnica de cultivo de aguas verdes (adición de microalgas a los sistemas) puede reducir este comportamiento (Bristow & Summerfelt, 1994;Cobcroft & Battaglene, 2009). Sin embargo, en Epinephelus marginatus se ha demostrado, que ni la reducción de las densidades de cultivo o diferentes metodologías utilizadas (aguas verdes) parecen tener efecto sobre la incidencia y tipología de malformaciones, requiriéndose más estudios sobre las causas de las malformaciones en esta especie (Boglione et al, 2009). Los juveniles de D. labrax exhibieron un alto nivel de malformación (81%) probablemente debido a la intensa actividad natatoria de los peces durante el crecimiento (Bardon et al, 2009).…”
Section: Otros Factoresunclassified
“…Also, the caudal skeleton development of the S. lalandi has been reported [29]. In addition, numerous studies have described the osteological development of other marine finfish species, such as Sparus aurata [30,31], Pagrus pagrus [32,33], Solea senegalensis [34,35], Dentex dentex [36], Argyrosomus regius [37], Epinephelus septemfasciatus [38] or Dicentrarchus labrax [39].…”
Section: Introductionmentioning
confidence: 99%